PENGARUH TEKNOLOGI INFORMASI, KOMPETENSI DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN CV GEMA TAMA DI SIDOARJO - Ketut Witara; Dwi Rifah Akmawati (STIE Mahardhika, 2020)
In the current era, every company must be able to make changes in the field of existing technology, so that later able to provide opportunities to improve the competitive advantage, further to support the company's business strategy, strive To establish the competency of human resources tailored to the areas in which they are handled, and in addition the training that is attended by employees will also affect the performance of an employee. All three are needed by one company CV. Gema Tama, which is a Distributor in the field of distributors, dealers and suppliers for laboratory needs. This research aims to know and analyze information and competency technology and simultaneous and partial work training on the employee performance of CV. Gema Tama. The phases of the study began from literary studies derived from the study of literature obtained from books, the Internet, and research that had been conducted previously. Followed by identification of questionnaire variables. After obtaining the questionnaire variables followed by designing a questionnaire. Data retrieval is conducted through questionnaires with saturated sample techniques and direct observation in the field. The results of field observations are explained through descriptive analysis, while data obtained from questionnaires is used to determine the influence of information technology, compensation, and job training on employee performance using Multiple linear regression analyses. In multiple regression analyses conducted several trials include: validity test, reliability test, classical assumption test, T test and test F. The results of the study are information technology, competence, and work training simultaneously positively influence and And able to explain the problems examined by researchers. So all the variables in this study have a positive and significant influence on employee performance